THE TRANSCULTURAL SEMANTICS IN THE WORKS BY JIN YONG - Seligey, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The works by Chinese Hong Kong writer Jin Yong (1924-2018) fare in the focus of Chinese readers’ attention as the exemplified wu-xia literature. His novels only recently became the object of literary studies within China, and are seen as an alternative to the literary discourse founded by the May Fourth Movement. The article is focused on the transcultural qualities of his prose. Though the imagery and background in his works are distinctly ancient Chinese, embodying the genre principle ancient clothing“’, a lot of techniques, including plot development, characters’ traits are highly reminiscent of Western literature, namely the works by A. Dumas and Shakespearean drama. The Chinese component in the work by Jin Yong is defined as threefold. The first and the most easily noticed is the language, drastically different from China mainland official Putonghua or Mandarin, seen as a complicated sometimes to eccentricity mixture of baihua and wenyan, the lively bright and colorful idiom literally breathing the Chinese tradition. The second component is defined by the titular wu-xia genre. The necessary core of Jin Yong’s novels imagery is the ethics and aesthetics of Chinese legendary “river and lake” chivalric society, with its strong and straightforward sense of justice, martial arts, romance, mysticism and complicated political intrigues. The third component is represented by the vast dialogue with the Chinese canon, from the ancient chronicles to the pre-modern novels such as “The Dream of the Red Chamber’’. It can take the form of creative rethinking and character modernization, almost always with distinct irony.